Corrosion Behavior of Zinc under Thin Solution Films of Different Thicknesses. Issue 9 (27th June 2018) - Somphotch, Chulaluk; Hayashibara, Hitoshi; Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : Zinc corrosion under 0.2 M NaCl solution films 5–800 μm in thickness was studied by electrochemical impedance spectroscopy (EIS). As-polished and rusted zinc plates obtained by exposure to a natural atmospheric environment for 1, 3, 6, and 12 months were used as working electrodes. The obtained EIS results were analyzed using a transmission line equivalent circuit to determine the charge transfer resistance ( R ct ), the reciprocal of which is proportional to the corrosion current density. For the as-polished zinc, the corrosion behavior is divided into three regions by the solution film thickness ( X f ). In Region I ( X f : 800–200 μm), R ct −1 is independent of X f and is approximately ten times smaller than that for carbon steel. In Region II ( X f : 200–25 μm), however, R ct −1 increases with decreasing solution thickness down to approximately 25 μm due to an enhancement of the oxygen diffusion (cathodic process) through the solution film. In Region III ( X f < 25 μm), further decreases in thickness reduce R ct −1 because the zinc dissolution (anodic process) is suppressed. In contrast, R ct −1 of the rusted zinc is independent of X f because the charge transfer process is strongly suppressed by the zinc corrosion products, which were identified as simonkolleite and zinc oxide.